Prokineticin 2 Upregulation in the Peripheral Nervous System Has a Major Role in Triggering and Maintaining Neuropathic Pain in the Chronic Constriction Injury Model. (5th January 2015) - Lattanzi, Roberta; Maftei, Daniela; Marconi, Veronica; Florenzano, Fulvio; Franchi, Silvia; Borsani, Elisa; Rodella, Luigi Fabrizio; Balboni, Gianfranco; Salvadori, Severo; Sacerdote, Paola; Negri, Lucia
Abstract : The new chemokine Prokineticin 2 (PROK2) and its receptors (PKR1 and PKR2 ) have a role in inflammatory pain and immunomodulation. Here we identified PROK2 as a critical mediator of neuropathic pain in the chronic constriction injury (CCI) of the sciatic nerve in mice and demonstrated that blocking the prokineticin receptors with two PKR1 -preferring antagonists (PC1 and PC7) reduces pain and nerve damage. PROK2 mRNA expression was upregulated in the injured nerve since day 3 post injury (dpi) and in the ipsilateral DRG since 6 dpi. PROK2 protein overexpression was evident in Schwann Cells, infiltrating macrophages and axons in the peripheral nerve and in the neuronal bodies and some satellite cells in the DRG. Therapeutic treatment of neuropathic mice with the PKR-antagonist, PC1, impaired the PROK2 upregulation and signalling. This fact, besides alleviating pain, brought down the burden of proinflammatory cytokines in the damaged nerve and prompted an anti-inflammatory repair program. Such a treatment also reduced intraneural oedema and axon degeneration as demonstrated by the physiological skin innervation and thickness conserved in CCI-PC1 mice. These findings suggest that PROK2 plays a crucial role in neuropathic pain and might represent a novel target of treatment for this disease.